Corporate Branding and Reputation Management in Malaysian Indigenous Manufacturing - Jaibalan, Harirajan (2012)
The purpose of this study is to examine and gain a better understanding of the Corporate Branding and Reputation Management in Malaysian Indigenous Manufacturing. This study focuses on Malaysian’s top car manufacturing company Perusahaan Automobile National (PROTON). PROTON has not been able to market the its products, namely, cars and spare parts in comparison to competitors. The researcher feels that it may be inappropriate Corporate Branding and Reputation Management or sheer absence of it. A study was conducted, involving Delphi method, to extract a useful path forward to steer the company for better Corporate Branding and Reputation management.